Avaliação da imunogenicidade de uma vacina comercial para a prevenção da infecção por Clostridioides difficile em suínos. - Victor Santos do Amarante (2024)
Clostridioides difficile infection is one of the main causes of diarrhea in humans snd animals. In pigs, C. difficile is an important cause of enteric disease in the first week of life, leading to economic losses due to reduced weight gain in affected animals. In addition to the importance of the pathogen in swine, the similarity between isolates from humans and animals suggests the possibility of zoonotic transmission. Toxigenic isolates of C. difficile produce toxins A (TcdA) and B (TcdB), the main virulence factors in the clinical picture of the disease. Measures to control the agent are made difficult by the formation of spores, which allows bacteria to remain viable in the most diverse environments for long periods. Therefore, the use of immunoprophylactic methods should be an alternative in preventing the occurrence of the disease. In 2021, the first commercial vaccine against C. difficile in pigs was made available on the on the brazilian market, consisting of inactivated toxins A and B. However, to date, there are no published studies evaluating this immunogen. The objective of this work was to evaluate the levels of serum antibodies in swine sows and neonatal piglets after ingestion of colostrum from females immunized with the commercial vaccine against C. difficile. Pregnant female pigs were divided into two groups. In group 1, 12 females were immunized at 6 and 3 weeks prior to parturition, while in the control group (n=6) the animals were vaccinated at the same interval with an immunogen containing the same adjuvant, but without toxoids A and B of C. difficile. Blood serum from sows was collected before each vaccination. Between 24 and 48 hours after birth, was collected serum from the sows and six piglets from each sow (n=72 piglets in group 1 and 36 in the control group). All serum samples were subjected to IgG detection through immunoenzymatic assays using fragments of the tcdA and tcdB toxins. The vaccine induced the formation of IgG anti-TcdA and TcdB antibodies in swine sows after the first and second dose (T1 and T2). Piglets passively immunized via colostrum showed higher levels of IgG against TcdA and TcdB antigens when compared to piglets suckled by dams in the control group. Therefore, it is possible to infer that a tested commercial vaccine is capable of inducing a humoral immune response against recombinant fragments of TcdA and TcdB from C. difficile in female pigs. Antibodies against these toxins in the serum of these animals are passively transmitted to neonatal piglets through colostrum.